Estimation of State-Dependent Utility Functions Using Survey Data - Evans, William N.; Viscusi, W. Kip (The Review of Economics and Statistics, 1991)
Surveys of individual's risk-dollar trade-offs illuminate not only the local trade-off rates, but also can be used to address more fundamental questions about the structure of utility functions. This largely unexplored empirical area is investigated by developing an econometric technique to estimate utility functions based on survey data on risk-dollar trade-offs for minor health effects. The empirical tests indicate that for all but one of the temporary health effects considered, consumers treat injuries as tantamount to a drop in income, implying that the health impact does not alter the structure of the utility function in a fundamental way. Copyright 1991 by MIT Press.